PEMODELAN PERILAKU KESELAMATAN KERJA, HUKUMAN, DAN PENGHARGAAN PADA PROYEK HOTEL ASTON MOJOKERTO - Feri Harianto; Fina Mufida; Diah Listyaningsih; Mohamad FN Aulady (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Poor safety behaviour is the leading cause of workplace accidents. One form of dangerous worker behaviour often seen in construction projects is not using PPE and not working according to procedures which are the biggest causes of workplace accidents. Risky behaviour has an essential role in explaining the possibility of work accidents. Therefore, to suppress dangerous behaviour, it is necessary to provide a stimulus to reduce the accident rate. One form of stimulation is given to construction workers, namely reward and punishment. This study aims to analyze the effect of punishment and reward on safety behaviour in construction project work. The population in this study are workers in the Aston Mojokerto Hotel building construction project. While the respondents as a sample were carpenters and coolies, totalling 36 people. The sampling technique used was the purposive sampling method. The variable in this study is the variable of punishment, appreciation functions as the independent variable, while the dependent variable is work safety behaviour. Analysis using multiple linear regression. Retrieval of data using a questionnaire. The study results explain that the punishment and reward variables significantly relate to the work safety behaviour variable. Reward and punishment variables simultaneously positively affect work safety behaviour variables. In contrast, the partial influence of punishment variables does not significantly impact workplace safety behaviour. This research implies the need for management in the field to carry out rewards and punishments for workers to improve work safety behaviour.